ORGANIZATIONAL CLIMATE AND ADMINISTRATIVE PERFORMANCE’S CONTRIBUTION TOWARD ACADEMIC SERVICE SATISFACTION IN VOCATIONAL SCHOOL (A STUDY ON PUBLIC VOCATIONAL SCHOOLS IN PALANGKARAYA) - Kartiwi, Asti Putri (EARR (Educational Administration Research and Review), 2017)
The core of the study was focused on the factors which affect service satisfaction, it includes the organizational climate and administrative performance. Based on this matter, the main problem revealed in this research was the measurement of organization climate and school administration performance’s contribution toward the satisfaction of academic service. The results showed: (1) organizational climate, was in the already good category. (2) Administrative performance, was in the high category. (3) The satisfaction of academic service, was in high enough category. (4) The results of relationship analysis showed that both variables have a positive and significant relationship. Recommendations given to schools was to improve the quality of school administration in relation to the quality assurance of academic services at public vocational schools in Palangkaraya.